Leonurine-Repressed miR-18a-5p/SOCS5/JAK2/STAT3 Axis Activity Disrupts CML malignancy - Liu, Hui-Min; Guo, Chun-Ling; Zhang, Yao-Fang; Chen, Jian-Fang; Liang, Zhi-Peng; Yang, Lin-Hua; Ma, Yan-Ping (Frontiers in Pharmacology, 2021)
Leonurine, an active natural alkaloid compound isolated from Herba leonuri, has been reported to exhibit promising anticancer activity in solid tumors. The aim of this study was to explore whether leonurine is able to inhibit chronic myeloid leukemia (CML) malignancy. Here, we found that leonurine dose dependently inhibited the proliferation, migration, colony formation and promoted apoptosis of CML cells. Furthermore, leonurine markedly reduced CML xenograft growth in vivo. Mechanically, leonurine upregulated SOCS5 expression, thus leading JAK2/STAT3 signaling suppression. Silencing of SOCS5 by its siRNA abrogated the effect of leonurine on CML cells, demonstrating that SOCS5 mediates the anti-leukemia effect of leonurine. Notably, we observed that miR-18a-5p was remarkably increased in CML cells. Treating CML cells with leonurine significantly decreased miR-18a-5p expression. Moreover, we found miR-18a-5p repressed SOCS5 by directly targeting its 3’-UTR. miR-18a-5p downregulation induced by leonurine reduced the biological activity of CML cells by relieving miR-18a-5p repression of SOCS5 expression. Taken together, leonurine exerts significant anti-leukemia efficacy in CML by regulating miR-18a-5p/SOCS5/JAK2/STAT3 axis.